Blunt thoracic aorta injuries, an Australian single centre's perspective. Issue 4 (28th January 2021) - Dinh, Krystal; Limmer, Alexandra; Ngai, Carlin; Cho, Tae; Young, Noel; Hsu, Jeremy
Abstract: Background: Blunt thoracic aortic injuries (BTAI) are potentially life‐threatening emergencies. The management paradigm has shifted from open repair to a predominantly endovascular approach. We evaluated the trends in managing BTAI at our centre over the last decade and compared them to current international guidelines. Methods: We retrospectively reviewed all patients who presented with BTAI to our level one trauma centre, Westmead Hospital, New South Wales, Australia between 1 January 2010 and 31 December 2019. Patient demographics, injury grade and location, imaging features, management details and outcomes were analysed. Results: BTAI is rare, with 39 patients identified at our institute over the last 10 years. Of these, seven died in the emergency department from their associated injuries (17.9%). Of the 32 survivors, 27 underwent surgical management with an endovascular stent‐graft placement, and the remaining five patients were treated non‐operatively. No patients were treated via an open surgical approach. All patients were diagnosed via computed tomography angiography. There were one death and two endoleaks amongst patients who underwent Thoracic endovascular aortic repair (TEVAR). The death occurred secondary to severe traumatic brain injury. Two patients illustrated neurological changes however these were associated with the original injury. No patients failed non‐operative management. Conclusion: This study demonstrates that at our level one trauma centre, patients with BTAI are managed in accordance with international guidelines. All patients underwent computed tomography angiography for diagnosis and grading of injury. All patients requiring surgical management underwent TEVAR. Furthermore, our data support that select patients with grade I injuries can safely be managed non‐operatively. Abstract : Blunt thoracic aortic injury is the second leading cause of death from blunt trauma. We look at how the management for blunt thoracic aortic injuries has changed over the years, as endovascular techniques improve.